Association of Parental Consanguinity with Severity of Cleft Lip and Palate. - Doshi, Sejal; Krishna, Vinod; Murugesan K, Murugesan K (Journal of Neonatal Surgery, 2025)
Background: Cleft lip and palate are among the most common congenital craniofacial anomalies worldwide. Parental consanguinity has been identified as a potential risk factor for congenital anomalies; however, its association with the severity of cleft deformities has not been extensively explored. Aim: To evaluate the association between parental consanguinity and the severity and pattern of cleft lip and palate. Materials and Methods: A hospital-based observational study was conducted on patients presenting with cleft lip and/or palate. Data regarding demographic details, degree of parental consanguinity, type of cleft, laterality, and presence of associated anomalies were recorded. Severity of cleft was categorized into cleft lip alone, cleft palate alone, unilateral cleft lip and palate, and bilateral cleft lip and palate. Statistical analysis was performed to assess associations between consanguinity and cleft severity. Results: A higher proportion of severe cleft patterns, particularly bilateral cleft lip and palate, was observed in patients born of consanguineous marriages. A statistically significant association was noted between degree of consanguinity and increasing severity of cleft deformity. Conclusion: Parental consanguinity is associated not only with the occurrence of cleft lip and palate but also with increased severity of the deformity. These findings highlight the importance of genetic counseling and public health education in populations where consanguineous marriages are prevalent..